Is There an Association Between Comprehensive Basic Science Examination Score and Acceptance into an Oral and Maxillofacial Surgery Residency Program?. Issue 11 (1st November 2018) - Momin, Mohmedvasim; Hawkins, Alexandria; Moles, Loren; Markiewicz, Michael R.; Miloro, Michael
Abstract : Sparse data exist regarding the association between applicants' Comprehensive Basic Science Examination (CBSE) scores and acceptance into an oral and maxillofacial surgery (OMFS) residency program. The aims of this study were to assess the association between applicants' CBSE scores and acceptance into one OMFS residency program; to determine the association between other applicant‐related variables and acceptance into the program; and to identify the mean CBSE score of accepted applicants by their dental schools' American Association of Oral and Maxillofacial Surgeons (AAOMS) district. For this retrospective data analysis conducted in 2017, the study sample consisted of applicants to the University of Illinois at Chicago OMFS residency program for the application cycles of 2013–14, 2014–15, and 2015–16. The primary predictor variable was CBSE score. The primary outcome variable was acceptance to the program. A total of 477 applicants were in the sample. In the multivariate analysis, CBSE score was found to be significantly associated with an increased chance of acceptance into the program (OR=1.11, 95% CI: 1.08, 1.15; p<0.001). Other variables associated with acceptance, though to a non‐significant degree, were age (p=0.01), dental school grade point average (GPA) (p=0.01), and number of externships completed prior to application (p=0.02). These findings may be useful for both applicants and program directors.